Performance assessment of buildings isolated by shape‐memory‐alloy rubber bearing: Comparison with elastomeric bearing under near‐fault earthquakes. Issue 4 (11th June 2013) - Gur, Sourav; Mishra, Sudib K.; Chakraborty, Subrata
ABSTRACT The shape‐memory‐alloy supplemented rubber bearing (SMARB) has been recently proposed as a superior alternative to traditional elastomeric bearing, such as lead‐rubber bearing (LRB), because of the dubious performance of conventional bearings under near‐fault earthquakes. The present study establishes the significant improvement of performances in SMARB over the LRB in isolating multi‐storeyed building frame against earthquakes. The response of the isolated building is evaluated through nonlinear dynamic time‐history analysis under a set of recorded, near‐fault, fault‐normal component of ground motions. The optimal characteristic strengths for both the bearings are obtained through parametric study. The robustness of the improved performances are studied under varying characteristics of the superstructure, isolation bearing, as well as scenarios of seismic loading. It is demonstrated that the improvement of isolation efficiency, accompanied by considerable reduction of peak and residual bearing displacements can be attained by the SMARB over the LRB. The SMARB is also found to be more effective in suppressing transference of high‐frequency components of ground motions to the floor acceleration, which is expected to be beneficial for frequency‐sensitive equipment, mounted on the floors. Copyright © 2013 John Wiley & Sons, Ltd.